Resistance spot welding of metal/carbon-fibre-reinforced plastics and applying silane coupling treatment. (3rd April 2018) - Nagatsuka, Kimiaki; Xiao, Bolyu; Wu, Lihui; Nakata, Kazuhiro; Saeki, Shuhei; Kitamoto, Yamato; Iwamoto, Yoshiaki
ABSTRACT: Dissimilar materials joining of SUS304 and carbon-fibre-reinforced plastics consisting of short fibres and thermoplastics was performed. The materials were joined by series resistance spot welding. The electrodes were pressed on the metal plate of the lap joint of metal/carbon-fibre-reinforced plastics. The SUS304 plate was heated by resistance heating, causing the thermoplastic near the interface to melt slightly because of heat conduction. SUS304 could be joined directly to carbon-fibre-reinforced polyamide and modified polypropylene, but not to polyphenylene sulphide. The joining area increased with an increase in the welding current and welding time, so did the tensile shear fracture load. Furthermore, the silane coupling agent treatment of SUS304 was highly effective in increasing the joining strength.